Surgical Anatomy of Facial Nerve in Rabbits - Abdullah Alhayani, Wissam; MA, Maher; Tariq Hammoodi, Omar (International Journal of Psychosocial Rehabilitation, 2020)
surgical and anatomical exploration to the extra-cranial distribution of facial nerve branches has a great surgical important to provide a clear model for nerve surgery. The present study was to illustrate of the anatomy of extra-cranial branches of facial nerve in rabbits. Eight adult New-Zealand rabbits (clinically healthy weighing from 2.5 to 3 kg,4 males and 4 females) had been studied in this investigation. The rabbits divided into two equal groups. In group (A) the rabbits were injected fresh after euthanasia, through common carotid artery and through jugular vein, by colored latex to investigate and reveal the course of the facial nerve in relation to facial blood vessels, while in group (B), the rabbits were injected by 10% formalin through common carotid artery and left for 2-3 days soaked with formalin and then dissected to follow up the branches of facial nerve. The results showed that, the facial nerve in rabbits is a good model for experimental surgery for nerve and anatomical little variance in its branches with man and other species.